2021
DOI: 10.1021/acs.chemmater.0c03259
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Oxygen Redox in the High-Lithium Material Li8SnO6

Abstract: Lithiated transition metal oxide cathode materials that combine oxygen-anion redox [O2 –/(O2) n−] with cation redox offer substantial capacities and higher voltage than cathodes without oxygen redox, but oxygen-anion redox is usually accompanied by the formation of peroxo or superoxo species that may cause oxygen release. To clarify the relationship between the oxygen release and peroxide and superoxide dimers without the complication of transition-metal redox, we performed density functional theory calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 55 publications
(94 reference statements)
2
21
0
Order By: Relevance
“…Local Li hops exhibit a range of activation energies of migration from 0.20 eV to 1.06 eV. In a previous DFT simulation study [27], it has been reported that hopping distances are in the range between 0.43 eV and 1.40 eV. Furthermore, the lowest activation energy of migration is found between two tetrahedral Li sites in agreement with the current simulation though there is an energy difference of 0.23 eV.…”
Section: Diffusion Of LI Ionssupporting
confidence: 90%
See 1 more Smart Citation
“…Local Li hops exhibit a range of activation energies of migration from 0.20 eV to 1.06 eV. In a previous DFT simulation study [27], it has been reported that hopping distances are in the range between 0.43 eV and 1.40 eV. Furthermore, the lowest activation energy of migration is found between two tetrahedral Li sites in agreement with the current simulation though there is an energy difference of 0.23 eV.…”
Section: Diffusion Of LI Ionssupporting
confidence: 90%
“…The main drawback of forming Li 2 O is capacity loss together with reduction in Coulombic efficiency [26]. Luo et al [27], performed density functional theory (DFT) simulations to show that the oxygen redox yields a high voltage plateau of over 4.0 V (vs Li/Li þ ). Furthermore, Li-ion diffuses fast in this material with an activation energy of 0.43 eV.…”
Section: Introductionmentioning
confidence: 99%
“…also reported that the shorter bond length and nonzero magnetic moments were consistent with the assignment as the O 2 − superoxide anion. [ 11 ] Therefore, the change of oxygen magnetic moment is closely related to the stability of the oxygen, especially at high voltage state. In addition, in Li‐rich cathode materials, Cho et al.…”
Section: Introductionmentioning
confidence: 99%
“…Li 8 IrO 6 is a ternary iridate reported among the A–T–O (A = alkali or alkali-earth element, T = Ce, Pr, Pb, Tb, Zr, Hf, Sn, Pt, Ir, Ru, Co, Ge, Si) system. This study is motivated by the fact that while interesting crystal structures and physical properties are reported for many noniridium Li 8 TO 6 compounds, the physical properties of Li 8 IrO 6 are still unknown. The crystal structure of Li 8 IrO 6 has been reported with a nonpolar space group R 3̅, which is isostructural to most compounds in the Li 8 TO 6 (T = Ce, Pr, Pb, Tb, Zr, Hf, Sn, Pt, Ru) series. However, it is different from some other Li 8 TO 6 (T = Co, Ge, Si) compounds adopting the polar space group ( P 6 3 mc ). The Li 8 RuO 6 compound was first reported as a tetragonal or rhombohedral structure, , but it was later determined to be Li-deficient Li 7 RuO 6 in a triclinic structure (space group P 1̅), which transforms into the rhombohedral structure (space group R 3̅) at 450 °C. , Confirming the crystal structure of Li 8 IrO 6 and understanding the reason for forming a nonpolar instead of a polar crystal structure will provide insights for existing and potentially novel Li 8 TO 6 compounds, which hold potentials as high-capacity Li-battery cathode materials, solid electrolytes, and CO 2 capture materials . Therefore, we launched an investigation to synthesize a phase-pure sample, understand the crystal and electronic structures, and determine the physical properties of Li 8 IrO 6 .…”
Section: Introductionmentioning
confidence: 99%